Animal Interiority: Sentience and Spatial Perception - Königk, Raymund (UI Scholars Hub, 2025)
Interior design has traditionally prioritised human experiences, often neglecting ecological and nonhuman perspectives on interiority. This anthropocentric focus limits the discipline's ability to address the spatial and sensory needs of nonhuman persons, including teleost fishes. It overlooks interiority as a universal and relational phenomenon shared by all living beings. This research challenges these boundaries by proposing a biosemiotic framework that integrates the body, interiority, and inhabitation as interdependent constructs shaped by physiological, mental, and environmental interactions. By developing Jakob von Uexküll's (1982) biosemiotic schema, the study investigates the sentient experiences of teleost fishes to establish interiority as a capability inherent in all life forms. It argues that interiority emerges not from constructed spaces but as an affective state shaped by sensory perceptions, environmental affordances, and the organism’s internal state. The case study on Betta splendens demonstrates that fishes exhibit spatial awareness, sensory agency, and dwelling behaviours, which underscores their capacity for interiority. This research extends the theoretical foundations of interior design by framing interiority as a shared ecological and physiological process rather than an exclusively human construct. It advocates for inclusive design practices that consider the lived experiences of nonhuman persons by challenging designers to create environments that foster well-being across species. By broadening interior design's scope, this study contributes to a more ethical and ecologically attuned approach to designing for inhabitation.